Curriculum, culture and music. Post-critical approximations to investigate a - Marlucy Alves Paraíso; Marlécio Maknamara (Universidad Politécnica Salesiana, 2012)
This work is aimed at pointing theoretical-methodological notes about post-critical curriculum investigations. It starts by highlighting some characteristics of post-critical theorization in education. Then, it clarifies how musical teachings can be productively investigated in a post-critical perspective. Considering musical discourses and its subjects'constitutions, it also highlights some procedures harmonized to post-critical researches that carry out discursive analysis inspired from Michel Foucault. Lastly, it brings aome final considerations about the commitment of investigating and writing education in a post-critical way, especially when investigating musical discourses.